Development of a Social Sciences E-Module Based on Local Wisdom with a Problem Solving Approach to Improve Students' Critical Thinking Ability - Suparmin, Suparmin; Warsono, Warsono; Segara, Nuansa Bayu; Subur, Hikmayani; Imran, Ahmad Fadhil (Journal of Educational Sciences, 2024)
This research aims to meet the needs of teachers and participants by presenting teaching materials in the form of social sciences e-modules based on local wisdom with a feasible and effective problem solving approach to improve students' critical thinking skills. This type of research is R&D which has been developed by Borg & Gall. Initial product development validated by media experts and material experts, initial field tests assessed from the responses of 2 teachers and 16 students, initial product revisions, main product tests assessed from the responses of 2 teachers and 27 students people, revision of the main product, operational field testing by giving pretests and posttests to 32 students, revision of the final product, and dissemination in junior high schools throughout Central Mamuju Regency. This research produced a social sciences e-module product based on local wisdom with a problem solving approach which was declared feasible and effective enough to improve students' critical thinking skills. The results of the independent t-test analysis show a sig. value (2-tailed) < 0.05, so the conclusion is that there is a difference in students' critical thinking abilities between the experimental class that uses the product and the control class that does not use the product.